1985
DOI: 10.1021/ac00286a048
|View full text |Cite
|
Sign up to set email alerts
|

Response of ion-selective field effect transistors to carbon dioxide and organic acids

Abstract: 1995excursion in the abundance of that isotope. The natural abundance of 34S is on the order of 4.0% and that of I5N is about 0.37%. It will, therefore, be possible to follow the dilution of 16N down to approximately a factor of 10 lower abundance than will be possible with Calculations based on these estimates suggest that 1 kg of %SO4 would label about 1 mile3 of air at the detection limit given a background level of about 8 pg/m3 sulfate. Sir:In recent years, the fabrication and study of various miniaturize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…0.01× PBS) the buffering capacity of the solution is reduced meaning that the system can become highly sensitive to small pH changes. For example, even the experimentalist breathing near the sample can result in elevated CO 2(g) dissolved into the sample and being detected 88 as per:…”
Section: Buffer Solutionmentioning
confidence: 99%
“…0.01× PBS) the buffering capacity of the solution is reduced meaning that the system can become highly sensitive to small pH changes. For example, even the experimentalist breathing near the sample can result in elevated CO 2(g) dissolved into the sample and being detected 88 as per:…”
Section: Buffer Solutionmentioning
confidence: 99%
“…Unfortunately, the benefits of these hydrogel film-based sensors quickly faded away with decreasing sensor sizes (hydrogel volumes). Long-term drifts were experienced in solutions with high concentration of interfering ions and when the concentrations of osmotically active species were fluctuating in the sample solution [92].…”
Section: Planar Microfabricated Electrodesmentioning
confidence: 99%
“…An additional source of potential instabilities is the spontaneous formation of a water film between the CP film and the IS membrane [101]. If this happens, the solid-contact electrodes behave similarly to planar electrodes fabricated with IFS of extremely small volume (hydrogel layer), i.e., the sensor becomes sensitive to transmembrane transport of water, CO 2 or O 2 [92].…”
Section: Planar Microfabricated Electrodesmentioning
confidence: 99%
“…A redox active layer is therefore of paramount importance for practical stability [74]. Lipophilic and redox active self-assembled monolayers have been shown to be useful systems for this purpose [75 -77], and it was found that without such layers a water film is present between the membrane and the solid contact [78,79]. Indeed, a thin water layer may be the source for substantial potential instabilities as the electrolyte composition of this layer may slowly change as a function of the sample composition [79].…”
Section: Solid Contactmentioning
confidence: 99%